A refined order release method for achieving robustness of non-repetitive dynamic manufacturing system performance - Chen, Yarong; Zhou, Hongming; Huang, Peiyu; Chou, FuhDer; Huang, Shenquan (Annals of operations research, 2022)
The operational quality and reliability of a manufacturing system is greatly influenced by uncertain or variable environments, therefore robustness is one of the most important indicators for measuring the operational quality of the non-repetitive dynamic manufacturing system. Controlling the order release to limit work in process at a stable level and protect throughput from variation is crucial to achieving robustness of manufacturing system performance. To deal with the influences of bottleneck severity and variable resource on system performance, a refined order release method is presented, which releases order periodically based on the corrected aggregate load and continuously based on the bottleneck buffer load. The operational quality of this method with the classical order release method under non-repetitive dynamic manufacturing system is compared by modeling and simulation. The results show that the refined order release method is more robust for general flow shop with higher protective capacity and resource variability.